In situ optical sequencing and structure analysis of a trinucleotide repeat genome region by localization microscopy after specific COMBO-FISH nano-probing - Stuhlmueller, Michael; Schwarz-Finsterle, Jutta; Fey, Evelyn; Lux, Johannes Thomas; Bach, Margund; Cremer, Christoph; Hinderhofer, Katrin; Hausmann, Michael; Hildenbrand, Georg Lars (Nanoscale, 2015)
Trinucleotide repeat expansions (like (CGG)n) of chromatin in the genome of cell nuclei can cause neurological disorders such as for example the Fragile-X syndrome. Until now the mechanisms are not clearly understood as to how these expansions develop during cell proliferation. Therefore in situ investigations of chromatin structures on the nanoscale are required to better understand supra-molecular mechanisms on the single cell level. By super-resolution localization microscopy (Spectral Position Determination Microscopy; SPDM) in combination with nano-probing using COMBO-FISH (COMBinatorial Oligonucleotide FISH), novel insights into the nano-architecture of the genome will become possible. The native spatial structure of trinucleotide repeat expansion genome regions was analysed and optical sequencing of repetitive units was performed within 3D-conserved nuclei using SPDM after COMBO-FISH. We analysed a (CGG)n-expansion region inside the 5′ untranslated region of the FMR1 gene. The number of CGG repeats for a full mutation causing the Fragile-X syndrome was found and also verified by Southern blot. The FMR1 promotor region was similarly condensed like a centromeric region whereas the arrangement of the probes labelling the expansion region seemed to indicate a loop-like nano-structure. These results for the first time demonstrate that in situ chromatin structure measurements on the nanoscale are feasible. Due to further methodological progress it will become possible to estimate the state of trinucleotide repeat mutations in detail and to determine the associated chromatin strand structural changes on the single cell level. In general, the application of the described approach to any genome region will lead to new insights into genome nano-architecture and open new avenues for understanding mechanisms and their relevance in the development of heredity diseases.
Gesehen am 26.11.2018